IMPLIKASI EKONOMI PERPANJANGAN HGU DAN HGB BAGI INVESTASI JANGKA PANJANG: STUDI LITERATUR TENTANG LEGALITAS DAN KEAMANAN BERUSAHA DI INDONESIA - Cecep Suhardiman; Gunawan Widjaja; Khalimi Khalimi (BORJUIS: JURNAL OF ECONOMY, 2025)
This study examines the economic implications of extending Land Use Rights (HGU) and Building Use Rights (HGB) on long-term investment in Indonesia through a literature review. The focus of the study is on the legality and security of doing business, which are crucial factors in creating legal certainty and a stable investment climate. The research method used is a literature review with sources such as legislation, scientific journals, and government reports. The results of the study indicate that the extension of HGU and HGB can increase the attractiveness of long-term investment by providing more stable land ownership guarantees and easier access to financing. However, challenges such as the potential for land monopolies, complex bureaucracy, and the risk of land conflicts and legal violations need to be addressed through management reforms that include digitalisation of services, simplification of procedures, and harmonisation of regulations. The success of these policies depends heavily on the synergy between legal certainty, good governance, and the protection of local community rights to support inclusive and sustainable economic development in Indonesia.